Identification and experimental validation of common genes associated with both pulmonary arterial hypertension and major depressive disorder - Yan, Yan; Hajary Sagor, Mohammad Ismail; Chen, Liang; Lin, Huakan; Gao, Gufeng; Lian, Guili; Xie, Liangdi (Frontiers in Psychiatry, 2025)
BackgroundPulmonary arterial hypertension (PAH) and major depressive disorder (MDD) frequently co-occur, worsening morbidity and mortality. The shared genetic and molecular substrates of this comorbidity remain unclear. This study investigated common differentially expressed genes (DEGs), convergent pathways, and candidate hub genes linking PAH and MDD.MethodsGene-expression datasets for PAH (GSE113439, GSE53408) and MDD (GSE44593, GSE54564) were obtained from GEO. After standardization, DEGs were identified with Limma, and intersected across diseases while retaining concordant expression trends. Functional enrichment was performed using Gene Ontology (GO). A protein–protein interaction (PPI) network was built to prioritize hub genes (CytoHubba), followed by feature selection with LASSO regression and additional machine-learning validation. Immune-cell infiltration was profiled to assess shared immunological alterations. An experimental rat model of PAH exhibiting anxiety- and depression-like behaviors was established, and hub-gene expression was validated by qPCR.ResultsForty-two common DEGs with consistent directions were identified. Network analysis and LASSO converged on six candidate hub genes; among these, CHD8, DDX42, and EIF3D were further supported by machine-learning validation. Immune-infiltration analysis indicated dysregulated immune landscapes in both PAH and MDD. In PAH rats, anxiety- and depression-like behaviors were observed, and qPCR confirmed altered expression of CHD8, DDX42, and EIF3D consistent with in-silico findings.ConclusionsThis integrative analysis highlights genetic and molecular links between PAH and MDD. CHD8, DDX42, and EIF3D emerge as candidate hub genes associated with the coexistence of these conditions, suggesting hypotheses for mechanistic follow-up and potential therapeutic targeting.